Wealth Distribution among Sasak Communities Through Inheritance: A Quest for Justice - Haji Munir, Zainal Arifin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This research describes the study of economic justice in the distribution of inheritance among the Sasak people, Lombok Indonesia. Economic justice is a value championed in the study of Islamic business law (al-fiqh al-muāmalah) by considering the traditions, national laws, and other laws that live in society.  Economic distribution justice is the main spirit in economic equality, one of which is through inheritance, which is also part of the maqāṣid al-sharī'ah value, namely hifz al-māl. This sociological research was conducted in several villages on Lombok Island: Sade, Bayan, Penujak, Teruwai, Pancor, and Aikmel. Data was collected through interviews, documentation, and observation of the community's perception, knowledge, and inheritance practice. In this study, it was found that the Sasak community prioritizes customary law, by considering Islamic law as a balance of justice. National law is only a last option when there is no way for dialog and discussion among the heirs. Sasak customary law, which is dominated by a patriarchal system, positions women lower than men. The presence of Islamic law opens the opportunity for women to enjoy economic justice (distribution). National law is used as an option when disputes and disagreements between heirs exist.